Analyzing decision making Metric conjoint analysis. - Louviere, Jordan J. (Newbury Park, [Calif.] ; London : SAGE, 1988)
This volume introduces the theory, method, and applications of one type of conjoint analysis technique. These techniques are used to study individual judgement and decision processes and forecast the chosen behavior of individuals or the populations they represent.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Consumer behavior -- Mathematical models; Decision making -- Mathematical models; Conjoint analysis (Marketing)